Antioxidant and antimicrobial collagen films incorporating Pickering emulsions of cinnamon essential oil for pork preservation. (15th September 2023) - Ran, Ruimin; Zheng, Tingting; Tang, Pingping; Xiong, Yongming; Yang, Changkai; Gu, Min; Li, Guoying
Highlights: Functionalized collagen films were prepared by adding CEO-based Pickering emulsions. The films showed enhanced thermal stability, light barrier, and water resistance. Kinetics of the release of CEO from films was fitted well by Peppas-Peppas model. Sustained release enhanced antimicrobial and antioxidant activities of the films. Functionalized collagen film extends shelf life of pork by an additional four days. Abstract: Cinnamon essential oil (CEO)-based Pickering emulsions were prepared using chitosan (CS) and soy protein isolate (SPI) colloid particles as stabilizers and genipin as cross-linker. Pickering emulsions have smaller particle sizes, higher stability, and encapsulation efficiency at a CS:SPI ratio of 1:4. The Pickering emulsion-modified collagen films showed enhanced thermal stability, UV-blocking properties, and water resistance. In addition, the antioxidant (DPPH scavenging activity, 18.35%-50.59%) and antimicrobial activities (inhibition zone, Escherichia coli, 0–1.85 cm; Staphylococcus aureus, 0–1.57 cm; Pseudomonas fluorescens, 0–1.34 cm) of the films were improved due to the sustained release of CEO, with the release kinetics following the Fickian diffusion of the Ritger-Peppas model. When the functionalized film was used for pork preservation, a four-day extension of shelf life was observed. Collectively, our findings suggest that Pickering emulsions provide great potential for the application of collagen film in pork preservation.